Effects of contrast between onsets of speech and other complex spectra - Coady, Jeffry A. (J Acoust Soc Am, 2003)
Previous studies using speech and nonspeech analogs have shown that auditory mechanisms which serve to enhance spectral contrast contribute to perception of coarticulated speech for which spectral properties assimilate over time. In order to better understand the nature of contrastive auditory processes, a series of CV syllables varying acoustically in F2 -onset frequency and perceptually from /ba/ to /da/ was identified following a variety of spectra including three-peak renditions of [e] and [o], one-peak simulations of only F2, and spectral complements of these spectra for which peaks are replaced with troughs. Results for three-versus one-peak (or trough) precursor spectra were practically indistinguishable, suggesting that effects were spectrally local and not dependent upon perception of precursors as speech. Effects of complementary (trough) spectra had complementary effects on perception of following stops; however, effects for spectral complements were particularly dependent upon the interval between precursor and CV onsets. Results from these studies cannot be explained by simple masking or adaptation of suppression. Instead, they provide evidence for the existence of processes that selectively enhance contrast between onset spectra of neighboring sounds, and these processes are relevant for perception of connected speech.